The Situation-Specific Theory of Heart Failure Self-Care: Revised and Updated. Issue 3 (May 2016) - Riegel, Barbara; Dickson, Victoria Vaughan; Faulkner, Kenneth M.
Abstract : Background: Since the situation-specific theory of heart failure (HF) self-care was published in 2008, we have learned much about how and why patients with HF take care of themselves. This knowledge was used to revise and update the theory. Objective: The purpose of this article was to describe the revised, updated situation-specific theory of HF self-care. Result: Three major revisions were made to the existing theory: (1) a new theoretical concept reflecting the process of s ymptom perception was added; (2) each self-care process now involves both autonomous and consultative elements; and (3) a closer link between the self-care processes and the naturalistic decision-making process is described. In the revised theory, HF self-care is defined as a naturalistic decision-making process with person, problem, and environmental factors that influence the everyday decisions made by patients and the self-care actions taken. The first self-care process, maintenance, captures those behaviors typically referred to as treatment adherence. The second self-care process, symptom perception, involves body listening, monitoring signs, as well as recognition, interpretation, and labeling of symptoms. The third self-care process, management, is the response to symptoms when they occur. A total of 5 assumptions and 8 testable propositions are specified in this revised theory. Conclusion: Prior research illustrates that all 3 self-care processes (ie, maintenance, symptom perception, and management) are integral to self-care. Further research is greatly needed to identify how best to help patients become experts in HF self-care.